The health hazards of chemical use in agriculture - London, Leslie (Department of Public Health and Family Medicine, 2018)
Photocopies of journal articles. * Agrichemical safety practices on farms in the Western Cape. London L. SA Med J 1994 ; 84 : 273-278. * Notification of pesticide poisoning in the Western Cape 1987 - 1991. London L, Ehrlich R, Rafudien S, Krige F, Vurgarellis P. SA Med J 1994 ; 84 : 269-272. * Critical Issues in agrichemical safety in South Africa. London L, Myers JE. Am J Ind Med 1995 ; 27(1) : 1-14. * Repeatability and validity of a field kit for estimation of cholinesterase in whole blood. London L, Thomson ML, Sacks S, Fuller B, Bachmann OM, Myers JE. Occupational and Environmental Medicine 1995; 52 : 57-64. * Biological Monitoring of workers exposed to organophosphate pesticides: Guidelines for field application. London L. Occupational Health Southern Africa July/August 1995 ; 1(4) : 13-17.